Silicon‐mediated cell wall modifications of sorghum root exodermis and suppression of invasion by fungus Alternaria alternata. (4th July 2018) - Bathoova, M.; Bokor, B.; Soukup, M.; Lux, A.; Martinka, M.
Abstract : Silicon (Si) is an element frequently associated with remedial properties in plant defence against various biotic stressors. Application of Si in plant–fungus interactions offers an intriguing research subject for its potential to reduce fungal disease‐related losses in agriculture. However, Si‐mediated changes in the plant metabolism must be first elucidated. The present microscopic study explores the effect of Si amendment on ultrastructural, cytological and anatomical aspects of the interaction between Sorghum bicolor 'Gadambalia' primary roots and the necrotrophic fungus Alternaria alternata . Bright‐field microscopy observations revealed that Si supplementation helped sorghum seedlings to restrict the growth of A. alternata, possibly by cell wall modifications of the root exodermis, limiting further fungal invasion. Ultrastructural analyses by transmission electron microscopy showed intense vesiculation in exodermal cells of inoculated roots. Fluorescence microscopy with suberin‐ and phenolic‐specific staining indicated a significant enhancement in the deposition of these substances in exodermal cell walls upon Si supplementation. The increased accumulation of phenolics in Si‐supplied plants was also confirmed by Raman spectroscopy. In conclusion, Si amendment seemed to alleviate the negative effect of A. alternata infection in sorghum roots, which is shown by restricted distribution of fungal hyphae in root tissues probably due to Si‐mediated deposition of suberin and phenolics in the exodermis.